2015
DOI: 10.1155/2015/638693
|View full text |Cite
|
Sign up to set email alerts
|

Influence ofGSTM1,GSTT1, andGSTP1Polymorphisms on Type 2 Diabetes Mellitus and Diabetic Sensorimotor Peripheral Neuropathy Risk

Abstract: Background and Aims. Diabetic neuropathy is a frequent complication of type 2 diabetes mellitus (T2DM). Genetic susceptibility and oxidative stress may play a role in the appearance of T2DM and diabetic neuropathy. We investigated the relation between polymorphism in genes related to oxidative stress such as GSTM1, GSTT1, and GSTP1 and the presence of T2DM and diabetic neuropathy (DN). Methods. Samples were collected from 84 patients with T2DM (42 patients with DN and 42 patients without DN) and 98 healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 44 publications
4
45
0
1
Order By: Relevance
“…Although, regression analysis in T2DM patients show that GSTM1 and GSTT1 genotypes are not associated with T2DM retinopathy development in the Southern Iranian population. Stoian A et al (2015) data suggest that GSTP1 gene polymorphisms may contribute to the development of T2DM in Romanian population. GSTM1, GSTT1, and GSTP1 gene polymorphisms are not associated with susceptibility of developing diabetic neuropathy in T2DM patients.…”
Section: Aims and Objectivementioning
confidence: 83%
“…Although, regression analysis in T2DM patients show that GSTM1 and GSTT1 genotypes are not associated with T2DM retinopathy development in the Southern Iranian population. Stoian A et al (2015) data suggest that GSTP1 gene polymorphisms may contribute to the development of T2DM in Romanian population. GSTM1, GSTT1, and GSTP1 gene polymorphisms are not associated with susceptibility of developing diabetic neuropathy in T2DM patients.…”
Section: Aims and Objectivementioning
confidence: 83%
“…15,16,20,33 For example, Stoian and colleagues (2015) reported no significant association between the GSTM1 and GSTT1 null genotypes and the development of type 2 diabetes mellitus (T2DM) in a Romanian patient population compared with a healthy control group (P = .96 for GSTM1; P = .21 for GSTT1). 23 Porojan and colleagues (2015) likewise found no increased frequency of the GSTM1 and GSTT1 null genotypes in the T2DM group compared with healthy controls (for GSTM1, OR = 1.44, CI = 0.85-2.45; P = .171; for GSTT1, OR = 0.85, CI = 0.44-1.67; P = .647). 34 In contrast, several studies have reported a significant association between the frequency of GSTM1 null and GSTT1 null genotypes and T2DM.…”
Section: Discussionmentioning
confidence: 95%
“…The thermal stability and enzyme activity of GSTP1 are decreased in the variant homozygote. 23,24 In the present study, we determined the genotype frequency of the GSTM1, GSTT1, and GSTP1 polymorphisms in liver transplant recipients and their association with the risk of NODM after transplant in a patient population in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous GST polymorphisms have been associated with an increased or decreased susceptibility to several diseases [39,[42][43][44][45], but only a few studies examined the association of GST polymorphisms and DR in T2DM patients ( Table 1). Cilenšek et al proposed a protective effect for the GSTM1-null genotype against retinopathy [46], explained by an up-regulation of other antioxidant enzymes, such as MnSOD [47].…”
Section: Glutathione S-transferases (Gsts)mentioning
confidence: 99%